Characteristics and Antioxidant Activity of Kebar Grass (Biophytum petersianum) Extract - Aminudin Aminudin; Nuri Andarwulan; Nurheni Sri Palupi; Iis Arifiantini (Biosaintifika: Journal of Biology & Biology Education, 2020)
Kebar grass (Biophytum petersianum Klotzsch.) has long been known by the locals of West Papua as medicinal plant that improves fertility. The objectives of this research were to identify and determine the antioxidant activity of kebar grass crude extract through conventional method and to analyze for its antioxidant activity. Extraction method used was conventional method, performed by mixing dry kebar grass with water and boiled until the volume shrunk to 1/3 of initial volume. Analized parameters were crude extract yield, qualitative phytochemical, total phenol and antioxidant activity. Research result showed extract crude yield value of 18.32±0.01%. Qualitative phytochemical contents were dominated by flavonoid, tannin, and saponin. Total phenolic content (TPC) of crude extract was 147±1.24 mgGAE/gdw (0.688±0.01 mgGAE/gfw). Crude extract antioxidant parameter was measured as the value of inhibition, AEAC, TEAC, and IC50 where each value respectively was as followed 42.0±0.047%, 69.93±2.19 mgAE/gdw (8.30±0.26 mgAE/gfw), 65.70±1.54 mgTE/gdw (7.80±0.18 mgTE/gfw) and 0.129±0.003 mgdw (257.75±4.90 mg/L). The contribution of kebar grass TPC content to antioxidant activity is 47.38% (equal to ascorbic acid) and 44.51% (equal to trolox) which means that almost half of kebar grass crude extract’s phenolic compound act as antioxidant. The results of this research can show that the kebar grass has potential as a source of multiple antioxidants, which acts as an analogue of vitamin C and vitamin E.  The antioxidant activity of the kebar grass extract can be the scientific basis for the use of kebar grass as a medicinal plant for infertility problems (curative) and as a functional food ingredient for antioxidant sources that prevent a decrease in reproductive performance (preventive).